2004
DOI: 10.1093/humrep/deh277
|View full text |Cite
|
Sign up to set email alerts
|

Obesity is associated with increased risk of first trimester and recurrent miscarriage: matched case-control study

Abstract: Obesity is associated with increased risk of first trimester and recurrent miscarriage.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

21
300
5
13

Year Published

2007
2007
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 524 publications
(339 citation statements)
references
References 16 publications
21
300
5
13
Order By: Relevance
“…Other issues relating to maternal obesity that were identified in the interviews and that are supported by published evidence relate to a higher incidence of shoulder dystocia, 5,22 longer duration of labour, 20 postoperative maternal morbidities such as wound infections and urinary tract infections, 15,5 length of stay and frequency of contact/level of care required because of coexisting and developing co-morbidities, 15,8 and complications with the infant during delivery and neonatally such as fetal distress, birth trauma, and feeding difficulties. 5,19,16,22 A number of issues raised in the interviews are not supported by published research; this may be because of the reliance of the majority of published studies on quantitative methodology and addressing specific biomedical impacts of maternal obesity, in particular relating to the outcome of pregnancy.…”
Section: Discussionmentioning
confidence: 75%
See 2 more Smart Citations
“…Other issues relating to maternal obesity that were identified in the interviews and that are supported by published evidence relate to a higher incidence of shoulder dystocia, 5,22 longer duration of labour, 20 postoperative maternal morbidities such as wound infections and urinary tract infections, 15,5 length of stay and frequency of contact/level of care required because of coexisting and developing co-morbidities, 15,8 and complications with the infant during delivery and neonatally such as fetal distress, birth trauma, and feeding difficulties. 5,19,16,22 A number of issues raised in the interviews are not supported by published research; this may be because of the reliance of the majority of published studies on quantitative methodology and addressing specific biomedical impacts of maternal obesity, in particular relating to the outcome of pregnancy.…”
Section: Discussionmentioning
confidence: 75%
“…The need for induction of labour and caesarean deliveries when the mother is obese or morbidly obese has been reported by numerous studies. 5,[11][12][13][14][15][16][17][18][19] Vahratian et al 20 discuss the need for more frequent administration of oxytocin to stimulate contractions during labour and a significant increase in emergency caesarean deliveries in the obese mother. Rode et al 21 also address a significant increase in emergency caesarean delivery rates, as well as overall caesarean rates, and elective caesareans.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…RM is one of the most disturbing women's health issues and several medical factors (chromosomal, anatomic, autoimmune, and metabolic disorders) have been reported as possible causes [4][5][6][7][8]. However, after standard investigations, up to 50% of these cases remain unexplained [2,9,10].…”
Section: Introductionmentioning
confidence: 99%
“…Human obesity is an important health concern, and many studies concerning assisted reproductive technologies (ART) have shown that obesity is associated with detrimental reproductive outcomes [1][2][3][4][5][6][7]. However, there are few reports on the influence of human obesity on embryonic vitrification.…”
Section: Introductionmentioning
confidence: 99%